2018 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM) 2018
DOI: 10.1109/aim.2018.8452709
|View full text |Cite
|
Sign up to set email alerts
|

Armband with Soft Robotic Actuators and Vibrotactile Stimulators for Bimodal Haptic Feedback from a Dexterous Artificial Hand

Abstract: The haptic sense relies upon a plurality of receptors and pathways to produce a complex perceptual experience of contact, pressure, taps, vibrations and flutters. This complexity is yet to be reproduced in haptic feedback interfaces that are used by people controlling a dexterous robotic hand, be it for limb-absence or teleoperation. The goal of the present bimodal haptic armband is to convey both low-frequency pressure changes and high-frequency vibrations from a dexterous robotic hand to a human's upper arm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Both layers were bonded together using a thin layer of Dragon-Skin 30. Full details about the design and manufacturing of the soft actuator armband can be found in the study by Abd et al, 20 where a psychophysics study demonstrated that human subjects could reliably discriminate between six discrete levels of pressure applied by the soft robotic armband.…”
Section: Fingertip Force Sensor Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Both layers were bonded together using a thin layer of Dragon-Skin 30. Full details about the design and manufacturing of the soft actuator armband can be found in the study by Abd et al, 20 where a psychophysics study demonstrated that human subjects could reliably discriminate between six discrete levels of pressure applied by the soft robotic armband.…”
Section: Fingertip Force Sensor Designmentioning
confidence: 99%
“…[15][16][17] The potential for malicious attacks causing artificial hand malfunction is one motivation of this article, which makes use of an i-limb prosthetic hand 18 that has been customized with tactile sensors in the fingertips 19 to enable an artificial sense of touch from a soft robotic armband worn by human test subjects. 20 Tactile information plays an important role when interacting with or manipulating different objects. [21][22][23] When amputees lose their hands, this afferent pathway of information is severed, and it can be difficult for them to control any object accurately without haptic feedback, using vision alone.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations